Is the Behavior of German Venture Capitalists Different? Evidence from the Neuer Mark - Tereza Tykvová (Goethe University Frankfurt, Center for Financial Studies (CFS), 2003)
Using a unique, hand-collected database of all venture-backed firms listed on Germanys Neuer Markt, we analyze the history of venture capital financing of these firms before the IPO and the behavior of venture capitalists at the IPO. We can detect significant differences in the behavior and characteristics of German vs. foreign venture capital firms. The discrepancy in the investment and divestment strategies may be explained by the grandstanding phenomenon, the value-added hypothesis and certification issues. German venture capitalists are typically younger and smaller than their counterparts from abroad. They syndicate less. The sectoral structure of their portfolios differs from that of foreign venture capital firms. We also find that German venture capitalists typically take companies with lower offering volumes on the market. They usually finance firms in a later stage, carry through fewer investment rounds and take their portfolio firms public earlier. In companies where a German firm is the lead venture capitalist, the fraction of equity held by the group of venture capitalists is lower, their selling intensity at the IPO is higher and the committed lock-up period is longer.
urn:nbn:de:hebis:30-10296
Keywords: D82; G24; G32; 330; IPO; Lock-up; Neuer Markt; Venture Capital